Una alfabetización científica tecnológica y cultural - Gallego Torres, Adriana Patricia; Zapata, Jair; Rueda Pinto, Monica (Revista Científica, 2011)
In this article there is discussed the need of a scientific technological and cultural literacy for the new millenium, orientated to mitigating the environmental, social and cultural challenges of our time. This literacy, it has to be vertebrada for the relations ctsc (science, technology, society and culture) and based from the reconstructions of the social history of the sciences and of the technologies, this way like also, in the sociology of the ciencias and the technologies.